2019
DOI: 10.3389/fpls.2019.01573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single and Combined Expression of Lysophosphatidic Acid Acyltransferase, Glycerol-3-Phosphate Acyltransferase, and Diacylglycerol Acyltransferase on Lipid Accumulation and Composition in Neochloris oleoabundans

Abstract: Microalgal lipids are promising feedstocks for food and biofuels. Since lipid production by microalgae is not yet economically feasible, genetic engineering is becoming a promising strategy to achieve higher lipid accumulation and productivities. Enzymes involved in the Kennedy pathway such as glycerol-3-phosphate acyltransferase (GPAT), lysophosphatidic acid acyltransferase (LPAT), and diacylglycerol acyltransferase (DGAT) catalyze key steps in the formation of triacylglycerol, which is the main constituent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
4
26
0
Order By: Relevance
“…Previous reports have investigated the impact of GPAT overexpression on elevating lipid content in various systems [ 14 , 15 ]. Here, we attempted to gain more insights into the mechanistic role of the identified GPAT2 in transgenic P. tricornutum .…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have investigated the impact of GPAT overexpression on elevating lipid content in various systems [ 14 , 15 ]. Here, we attempted to gain more insights into the mechanistic role of the identified GPAT2 in transgenic P. tricornutum .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated that the reaction catalyzed by LPAT1 is one of the rate-limiting steps in TAG synthesis in C. merolae . Recently, Muñoz et al [ 24 ] investigated the ER-localized LPAT function of Acutodesmus obliquus in Neochloris oleoabundans cells. The authors showed that TAGs were significantly accumulated compared with the wild type under nitrogen-deficient conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Current genetic engineering strategies to improve microalgal productivity of lipids, which are the precursors for biofuel production, have often resulted in reduced biomass production and/or growth rate. At least to some extent this is because the supply of carbon or energy is insufficient to meet the increased demands of engineered strains (Figure 1) [4][5][6]. Thus, to overcome carbon or energy shortage, further major improvements in microalgal productivities will require extensive rewiring of the upstream metabolic pathways such as carbon fixation, as well as the generation of ATP and reducing power by photosynthesis.…”
Section: Towards Improving Upstream Photosynthetic and Co 2 Fixation Metabolismmentioning
confidence: 99%